The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/2526-8910.ctoao232830642
|View full text |Cite
|
Sign up to set email alerts
|

Modified Hospital Elder Life Program in the emergency department of a public university hospital: a multicomponent intervention program for preventing delirium

Abstract: Objective To evaluate the feasibility of implementing an adaptation of the Hospital Elder Life Program (HELP) with the participation of family caregivers in a public university hospital. Method Descriptive exploratory pilot study developed with 30 hospitalized patients and their caregivers. Registration Forms were applied to identify risk factors for delirium, to select intervention protocols, and track implementation. Participants' level of satisfaction and barriers to implementing the program were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Family carers in one study in the ICU setting also suggested a communication resource box could be shared by family carers and staff (Bannon et al., 2018). Lack of access to glasses and hearing aids was identified as a barrier to communication and family carer ability to support delirium management (Assis et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Family carers in one study in the ICU setting also suggested a communication resource box could be shared by family carers and staff (Bannon et al., 2018). Lack of access to glasses and hearing aids was identified as a barrier to communication and family carer ability to support delirium management (Assis et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Based on a consensus approach, the studies included in this review were found to be of moderate (score of 3) to high quality (score of 5; Table 1). 23 Four studies were conducted in the United States of America [27][28][29][30] ; and one each in Brazil, 31 Chile 32 and South Korea. 33 Study designs included one randomised controlled trial, 32 two quasi-experimental pre-post-test designs, 29,30 two descriptive exploratory studies, 28,31 one qualitative study 33 and one mixed-method design.…”
Section: Resultsmentioning
confidence: 99%
“…23 Four studies were conducted in the United States of America [27][28][29][30] ; and one each in Brazil, 31 Chile 32 and South Korea. 33 Study designs included one randomised controlled trial, 32 two quasi-experimental pre-post-test designs, 29,30 two descriptive exploratory studies, 28,31 one qualitative study 33 and one mixed-method design. 27 One study did not report carer characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations